The “No Reflective Loss” Principle: Towards to the “Priority Rule” - Zhao Jiyang (SHS Web of Conferences, 2024)
This essay discusses how the “no reflective loss” principle has developed and its current problem. “No reflective loss” principle, introduced in Prudential Assurance Co Ltd v Newman Industries Ltd (No.2), developed in Johnson v Gore Wood & Co, is gradually becoming unreasonable, since the application of it has expanded to an exaggerated extent. In the case Sevilleja v Marex Financial Ltd, “no reflective loss” principle was been narrowed, but its fundamentalism brought other issues. Because of the poor policy considerations of “no reflective loss” principle, cases concerning reflective loss are more suitable to be resolved using the “priority rule”. The "Priority rule" not only protects the autonomy of corporate governance, but also protects the interests of shareholders who are overlooked in "no reflective loss" principle and also prevents the problem of double recovery, so the future of this principle is brighter than that of “no reflective loss.” Although this essay has discussed the "priority rule" mainly in two scenarios, there are certainly some refinements to applying it in practice. Further studies should be carried out on a practical level, relating to specific cases, by implementing this principle in existing cases.